The Effect of Jati Belanda Leaves (Guazuma ulmifolia Lamk.) Ethanol Extract on Microscopic Features of Atherosclerotic Animal Modelâ€™s Aorta - Ryan J. Permana; Cherry Azaria; Rosnaeni Rosnaeni (Universitas Kristen Maranatha, 2016)
â€œJati Belandaâ€ leaves (Guazuma ulmifolia Lamk.) possesses antidyslipidemia effect and in this study we assessed the effect of